Asiaticoside improves depressive-like behavior in mice with chronic unpredictable mild stress through modulation of the gut microbiota - Ren, Qingyi; He, Chenxi; Sun, Yuhong; Gao, Xiaowei; Zhou, Yan; Qin, Tao; Zhang, Zhuo; Wang, Xiaodong; Wang, Jun; Wei, Siping; Wang, Fang (Frontiers in Pharmacology, 2024)
Background Asiaticoside, the main active ingredient of Centella asiatica, is a pentacyclic triterpenoid compound. Previous studies have suggested that asiaticoside possesses neuroprotective and anti-depressive properties, however, the mechanism of its anti-depressant action not fully understood. In recent years, a growing body of research on anti-depressants has focused on the microbiota-gut-brain axis, we noted that disruption of the gut microbial community structure and diversity can induce or exacerbate depression, which plays a key role in the regulation of depression. Methods Behavioral experiments were conducted to detect depression-like behavior in mice through sucrose preference, forced swimming, and open field tests. Additionally, gut microbial composition and short-chain fatty acid (SCFA) levels in mouse feces were analyzed 16S rRNA sequencing and gas chromatography-mass spectrometry (GC-MS). Hippocampal brain-derived neurotrophic factor (BDNF) and 5-hydroxytryptamine receptor 1A (5-HT1A) expression in mice was assessed by western blotting. Changes in serum levels of inflammatory factors, neurotransmitters, and hormones were measured in mice using ELISA. Results This study revealed that oral administration of asiaticoside significantly improved depression-like behavior in chronic unpredictable mild stress (CUMS) mice. It partially restored the gut microbial community structure in CUMS mice, altered SCFA metabolism, regulated the hypothalamic–pituitary–adrenal axis (HPA axis) and inflammatory factor levels, upregulated BDNF and 5-HT1A receptor protein expression, and increased serum serotonin (5-hydroxytryptamine, 5-HT) concentration. These findings reveal that asiaticoside exerts antidepressant effects via the microbiota-gut-brain axis. Conclusions These results suggested that asiaticoside exerts antidepressant effects through the microbiota-gut-brain axis in a CUMS mouse model.